Anti-monocyte globulin in allogeneic transplantation of hematopoietic stem cells - Yu. R. Zalyalov; B. A. Ganapiyev; V. G. Potapenko; N. B. Mikhaylova; B. V. Afanasyev (Онкогематология)
Acute graft-versus-host disease (GFHD) and graft rejection reaction (GRR) early in the post-transplantation period are main complications of allogeneic transplantation of hematopoietic stem cells. We analyzed the incidence of principal early complications in 109 patients with various oncohematologic diseases who underwent 112 allogeneic transplantations of hematopoietic stem cells from related and unrelated donors with myeloablative and non-myeloablative regimens of conditioning with and without use of anti-monocyte globulin. Application of anti-monocyte globulin provides effective control of acute GFHD without increment of disease relapsing risk and lowers the incidence of GRR to 7%. So, results of our study showed that usage of anti-monocyte globulin with conditioning regimens for patients who habe undergone allogeneic transplantation of hematopoietic stem cells, allows to effectively decrease the incidence of early posttransplantation complications. Consequently, that increases the 4-year overall survival of these patients as compared with patients who did not undergo the use of anti-monocyte globulin.